Synergistic antifungal effects of botanical extracts against Candida albicans - Eunjin Cho; Kenneth Acosta; Joshua Henkin; Rinat Abzalimov; Ilya Raskin (PLoS ONE, 2026)
Antifungal resistance is growing increasingly more common due to the widespread use of limited number of antifungal compounds classes. Plant extracts have been used and studied for thousands of years as antifungal therapeutics alone or in combination with other natural products. This study investigated the synergistic effects of combining ethanolic extracts from nine plants with documented antifungal activity to identify natural and more powerful antifungal treatments against Candida albicans . Using checkerboard microdilution assays, 11 out of 15 combinations exhibited additive or synergistic interactions (fractional inhibitory concentration index, FICI < 1). The strongest synergy was observed between Alpinia officinarum and Hydrastis canadensis with MIC 90 FICI = 0.08 and MIC 50 FICI = 0.05. Combinations involving H. canadensis , Eucalyptus globulus, and Punica granatum produced the most synergistic effects with other tested extracts and with each other. Combining putative active compounds from each of these three extracts demonstrated synergistic antifungal activity, with the strongest synergy observed with berberine (from H. canadensis ) and punicalagin (from P. granatum) with MIC 90 FICI = 0.31 and MIC 50 FICI = 0.13. Eucalyptol did not produce any significant antifungal activity so E. globulus extract was fractionated to identify its main antifungal compounds. UPLC-MS analysis determined that the most active fractions were primarily made up of hydrolysable tannins which produced strong synergy when combined to berberine with MIC 90 FICI = 0.31 and MIC 50 FICI = 0.25. The combinations of berberine with punicalagin and berberine with the E. globulus high tannin fraction F5 displayed antifungal activity against C. albicans with MIC 90 concentrations of 2–16 µg/mL, which are comparable to MIC 90 concentration for econazole of 0.5–8 µg/mL. These results suggest that phytochemical mixtures containing different classes of antifungal compounds can approach the efficacy of commercial antifungals and may serve as effective alternatives.